Impact of interlayer application on band bending for improved electron extraction for efficient flexible perovskite mini-modules. (July 2018) - Pisoni, Stefano; Fu, Fan; Widmer, Roland; Carron, Romain; Moser, Thierry; Groening, Oliver; Tiwari, Ayodhya N.; Buecheler, Stephan
Abstract: The development of highly efficient lightweight flexible perovskite solar cells (PSCs) opens the way to high-throughput roll-to-roll manufacturing processes and new applications such as building integration and mobile products. Flexible PSCs are generally realized on small areas (< 0.2 cm 2 ), far from technology commercialization where modules-scale is necessary. In this work, we demonstrate highly efficient n-i-p PSCs grown on flexible substrates by proper interface engineering for improved electron extraction. We compared spin coated PEIE and vacuum deposited LiF as interlayers between Al-doped ZnO, as transport conductive oxide (TCO), and thermally evaporated C60, as electron transport layer (ETL). Once interlayers are applied, we observed a favorable band bending at TCO interface which results in enhanced charge extraction and lower recombination losses. We achieved flexible PSCs with stabilized efficiencies of 14.8%, both with PEIE and LiF interfacial modifications. In addition, we developed a flexible perovskite mini-module with stabilized efficiency of 10.5% onto an aperture area larger than 10 cm 2 . The monolithic interconnections are entirely obtained by highly accurate and reliable laser scribing methods. A geometric fill factor as high as ~ 94% is achieved, with a dead area width of ~ 250 µm. Graphical abstract: fx1 Highlights: Flexible perovskite solar cells with efficiency of 14.8% by interfacial modification between C60 and Al-doped ZnO. Beneficial band bending at ETL/TCO interface obtained by interlayer and verified by UPS measurements. All-laser scribed flexible perovskite mini-module with efficiency of 10.5%, aperture area > 10 cm 2 and GFF ∼ 94%.